LEGAL REFORM DALAM PENJATUHAN SANKSI TERHADAP ANAK PELAKU KEJAHATAN - Ni Nyoman Juwita Arsawati; Anak Agung Ayu Ngurah Tini Rusmini Gorda (Universitas Pendidikan Nasional, 2018)
The child needs to be protected both physically and spiritually, especially when the child is a criminal. Children to be accountable for their actions, not separated from the imposition of criminal punishment of imprisonment. The imposition of imprisonment on children is irrelevant compared to the crime rate, and it seems that imprisonment does not deter the perpetrator. It can be attributed to a child's crime similar to that of an adult whether in quantity or quality. This situation certainly raises issues both philosophically, juridically and sociologically. It is deemed necessary to reform the criminal law in the face of children as perpetrators of crime, deprivation of liberty by placing children in prison, unable to provide protection from the deprivation of the rights of children as opposed to the values of Pancasila as stipulated in the second precept